Combining river replenishment and restrictions on groundwater pumping to achieve groundwater balance in the Juma River Plain, North China Plain - Cui, Weizhe; Hao, Qichen; Xiao, Yong; Zhu, Yuchen; Li, Jianfeng; Yuanjing Zhang, (Frontiers in Earth Science, 2022)
In recent years, to alleviate the decline in groundwater levels, extensive restrictions on groundwater pumping have been implemented in the North China Plain (NCP). In September 2018, a large-scale ecological water replenishment project was executed involving 22 rivers and lakes. How to adjust the layout of reduction on groundwater pumping within the context of ecological water replenishment is a key issue to be addressed in the study of groundwater level recovery in the NCP. This study adopted the Juma River Plain in Baoding city as a case study, established a numerical model of river replenishment of groundwater, predicted groundwater level changes over the next 15 years (2021–2035) and quantitatively calculated the impact of river replenishment on groundwater levels. To achieve the goal of an overall groundwater balance by 2035, a suitable groundwater pumping restriction scenario was defined based on the impact of river replenishment on groundwater levels. The results indicated that by 2035, the relative rise in groundwater levels attributed to river replenishment and restrictions on groundwater pumping could reach 3.51 and 2.28 m, respectively. River replenishment significantly impacts groundwater levels, especially those near the river. Under the current groundwater exploitation conditions, river replenishment could ensure groundwater level recovery near the river, which accounts for 15% of the total study area. The goal of an overall groundwater balance by 2035 could be achieved if restrictions on groundwater pumping were superimposed, with an average annual reduction of 56 million m3. This study provides valuable insights into groundwater management across the NCP. The proposed methods are useful for the management of other depleted aquifers recharged via ecological water replenishment.